2014
DOI: 10.1142/s0192415x14500153
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities ofCuscuta chinensisSeeds in Mice

Abstract: The seeds of Cuscuta chinensis, Cuscutae Semen, are commonly used as a medicinal material for treating the aching and weakness of the loins and knees, tonifying the defects of the liver and the kidney, and treating the diarrhea due to hypofunction of the kidney and the spleen. Since aching and inflammation are highly correlated with such diseases, the aim of this study is to investigate the possible antinociceptive and anti-inflammatory mechanisms of the seeds of C. chinensis. The antinociceptive effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…Although hyperoside and quercetin have been detected in both of seeds and whole plant of C. campestris , their amounts and the other flavonoids are different [4,20]. Hyperoside have been shown to increase the level of heme oxygenase-1, an important enzyme in antioxidant defense systems to reduce oxidative stress [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although hyperoside and quercetin have been detected in both of seeds and whole plant of C. campestris , their amounts and the other flavonoids are different [4,20]. Hyperoside have been shown to increase the level of heme oxygenase-1, an important enzyme in antioxidant defense systems to reduce oxidative stress [21].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin has shown a high antioxidant activity by reducing the production of reactive oxygen species and nitric oxide [20,22]. The methanol extract of the seeds of Cuscuta chinensis containing hyperoside, quercetin and kaempferol have been reported to increase the activities of SOD, GPx and GRd in the liver [4]. Hyperoside and quercetin have been shown to exhibit hepatoprotective effect against CCl 4 -induced liver injury [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the genus Cuscuta , the whole plants of Cuscuta arvensis (Koca et al, ), Cuscuta campestris (Agha et al, ; Ghule et al, ), and C. chinensis (Akbar et al, ); the seeds of C. chinensis (Liao et al, ); and the stems of C. reflexa (Pal et al, ) all show analgesic effects in different animal models. Koca et al () reported that the methanol extract of Cu.…”
Section: Pharmacologymentioning
confidence: 99%